Formulation Optimization and Evaluation of Ocular Inserts Prepared with Sulfoxyamine Modified Chitosan - Jadhav, Dr. Rahul Laxman (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: The aim of the present research work is to use our previously modified chitosan in formulation development and optimization of ocular insert. Materials and Methods: Ocular insert was made from an aqueous dispersion of ofloxacin, polyvinyl alcohol (PVA), modified chitosan, sodium alginate, and dibutyl phthalate by the solvent casting method. It was coated with Eudragit S100 and evaluated for drug-excipient interaction, physicochemical characteristics, and microbiological and in vitro release studies. In the present study, 32 full factorial designs were employed with the help of Design-Expert software to study the effect of independent variables, i.e., effects of PVA amount (X1) and modified chitosan amount (X2) on the dependent variables, i.e., % moisture absorption and mucoadhesion time. Results and Discussions: In Fourier transform infrared study, a major characteristic peak of ofloxacin was found in the entire coated ocular inserts, confirming the presence of the drug in the polymer without interaction. The result of the differential scanning calorimetric (DSC) study shows the thermogram of pure ofloxacin exhibited a sharp endothermic peak at 276.25°C and heat of fusion of 41.97J/G, which corresponds to its melting point. DSC thermogram of the physical mixture, and formulation do not shows peak of pure drug.This revealed that ofloxacin was molecularly dispersed in polymer. The weight and thickness of the inserts were in the range of 3.23–5.75 mg and 0.11–0.21 microns, respectively, for different formulations. The in vitro drug permeation studies were carried out using an all-glass modified Franz diffusion cell. The drug concentration and mucoadhesion time of the ocular insert were found satisfactory. The ocular insert coated with Eudragit S100 showed maximum drug permeation through Millipore membrane and excised goat cornea compared to other formulation. In goat corneas permeation studies, the formulation OFXF8 showed a 17.06% release at the end of 4 h which is more as compared to other formulation. Ocular inserts using PVA and modified chitosan as a polymer were successfully prepared and can be effectively used for sustained ocular delivery over a period of 24 h. An optimization study was conducted using 32 factorial design. Conclusion: Based on these findings, it was concluded that the designed ocular inserts are a realistic alternative to conventional eye drop by virtue of its ability to improve bioavailability and improving patient compliance